1998
DOI: 10.1007/s007010050076
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Tranexamic Acid and Nimodipine in the Pre-operative Treatment of Ruptured Intracranial Aneurysms

Abstract: In the scope of a late intervention policy on ruptured intracranial aneurysms, on D.+12 on an average, we first used tranexamic acid, at moderate doses: 3 g orally or 1.5 g intravenously per day. We, subsequently, added nimodipine, usually 240 mg orally per day or 2 mg intravenously per hour. The medical treatment consisted of amply sufficient hydration, and in systematic and regular administration of analgesics and sedatives. Hypotension was absolutely avoided; if necessary, an antihypertensive treatment was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…5,17,27,43,46,50,53,58 Nevertheless, although rebleeding occurs in 15 to 30% of patients during the first 2 weeks of conservative treatment, the influence of early intervention on overall outcome is still a matter of debate. 37,52,58 Our data clearly show that close collaboration with local referring hospitals permits effective application of a protocol for immediate diagnosis and transfer of patients with SAH to neurosurgical centers on a large scale. Furthermore, data show that given such an organization, expedited treatment of aneurysms in patients in all clinical grades can virtually eliminate in-hospital rebleeding after the 1st day of SAH.…”
Section: Ultraearly Rerupturementioning
confidence: 88%
See 1 more Smart Citation
“…5,17,27,43,46,50,53,58 Nevertheless, although rebleeding occurs in 15 to 30% of patients during the first 2 weeks of conservative treatment, the influence of early intervention on overall outcome is still a matter of debate. 37,52,58 Our data clearly show that close collaboration with local referring hospitals permits effective application of a protocol for immediate diagnosis and transfer of patients with SAH to neurosurgical centers on a large scale. Furthermore, data show that given such an organization, expedited treatment of aneurysms in patients in all clinical grades can virtually eliminate in-hospital rebleeding after the 1st day of SAH.…”
Section: Ultraearly Rerupturementioning
confidence: 88%
“…28,30,57 Nevertheless, some clinicians still adhere to this treatment policy. 37,48,52 The object of this randomized prospective study was to assess the efficacy of short-term antifibrinolytic treatment with tranexamic acid in preventing rebleeding. 32 …”
mentioning
confidence: 99%
“…A number of studies using both antifibrinolytics and either nicardipine or nimodipine reported decreased rebleeding, no increase in ischemic deficits, and improved outcomes [15,26,28,41,42]. Rebleeding rates ranged from 7% to 13% and mortality ranged from 11% to 12%.…”
Section: Other Non-randomized Clinical Trialsmentioning
confidence: 98%
“…No differences have been found between EACA and TXA with respect to preventing early recurrence of aSAH, overall pre-operative mortality rates, and side effects [28,53]. An increased incidence of hydrocephalus in patients on long-term antifibrinolytics has been reported [14,21,[54][55][56][57][58].…”
Section: Complications and Side Effectsmentioning
confidence: 99%
See 1 more Smart Citation